The gut microbiota–bile acid axis: A potential therapeutic target for liver fibrosis - Zhang, Yu-Lin; Li, Zhen-Jiao; Gou, Hong-Zhong; Song, Xiao-Jing; Zhang, Lei (Frontiers in Cellular and Infection Microbiology, 2022)
Liver fibrosis involves the proliferation and deposition of extracellular matrix on liver tissues owing to various etiologies (including viral, alcohol, immune, and metabolic factors), ultimately leading to structural and functional abnormalities in the liver. If not effectively treated, liver fibrosis, a pivotal stage in the path to chronic liver disease, can progress to cirrhosis and eventually liver cancer; unfortunately, no specific clinical treatment for liver fibrosis has been established to date. In liver fibrosis cases, both the gut microbiota and bile acid metabolism are disrupted. As metabolites of the gut microbiota, bile acids have been linked to the progression of liver fibrosis via various pathways, thus implying that the gut microbiota–bile acid axis might play a critical role in the progression of liver fibrosis and could be a target for its reversal. Therefore, in this review, we examined the involvement of the gut microbiota–bile acid axis in liver fibrosis progression to the end of discovering new targets for the prevention, diagnosis, and therapy of chronic liver diseases, including liver fibrosis.